Efficacy of bortezomib in non‐IgM type I cryoglobulinaemic vasculitis: a single‐centre retrospective case series. (24th September 2018) - Lobbes, Hervé; Grobost, Vincent; Lemal, Richard; Rieu, Virginie; Le Guenno, Guillaume; Ruivard, Marc
Abstract: Introduction: Treatment of non‐IgM type I cryoglobulinaemic vasculitis (CV) is challenging. Corticosteroids are first‐line therapy, but relapses are frequent leading to therapeutic escalation. Bortezomib is a proteasome inhibitor with rapid effect on monoclonal component. However, its use in non‐IgM type I CV has been barely reported. Objective: To assess the efficacy of bortezomib in non‐IgM type I CV. Method: Single‐centre case series of four patients with non‐IgM type I CV treated with bortezomib monotherapy. Results: Two men and two women, 60‐84 years old, received bortezomib monotherapy. Monoclonal component was IgG‐λ (n = 2), IgA‐λ and IgG‐κ. Clinical features were necrotic rash (n = 3), synovitis (n = 3) and sensitive neuropathy (n = 2). CV was refractory to corticosteroids (n = 4), cyclophosphamide (n = 3) and rituximab (n = 2). Three patients experienced dramatic clinical improvement with undetectable cryoglobulin after three cycles (bortezomib 1.3 mg/m 2 weekly). Each patient relapsed 4‐18 months after treatment discontinuation. Bortezomib was unsuccessful after four cycles in one patient. Bortezomib toxicity included one pneumonia and 1 case of worsening neuropathic pain. Conclusion: Bortezomib in monotherapy should be considered as a valuable option in refractory non‐IgM type I CV because of its swift efficacy and acceptable tolerance profile.